Comparison of Janani Suraksha Yojana (JSY) and augmented Arogya Laxmi scheme (ALS) in improving maternal and child health outcomes in urban settlements of Hyderabad, South India - E R Nandeep; Raja Sriswan Mamidi; Sreenu Pagidoju; Spandana Pamidi; Mahesh Kumar Mummadi; Venkata Raji Reddy G; Chinta Khadar Babu; Samarasimha Reddy N; JJ Babu Geddam (BMC, 2024)
Abstract Background India accounts for the largest number of global neonatal deaths with around 20 per 1000 live births. To improve the utilization of government services for institutional deliveries, Augmented Arogya Laxmi Scheme (ALS) was launched in Telangana state of southern India. This study assessed the effectiveness of the Janani Suraksha Yojana (JSY), which combines cash assistance with delivery and post-delivery care, in comparison to ALS in improving the outcomes related to antenatal, natal, and postnatal care in urban settlements of Hyderabad, Telangana, southern India. Methods This was a two-year cross-sectional study conducted in 14 urban settlements of Hyderabad city from September 2017- August 2019. All mothers delivered during the 18 months preceding the survey were enrolled after a written informed consent. Field investigators collected data on variables related to socio-demographic characteristics, awareness, and utilization of JSY and ALS programs. Variables related to antenatal history, antenatal care, complications during birth, delivery outcomes, newborn care, and postnatal care till 28 days were assessed. We used multivariable logistic regression model to examine the association between the different maternal, child, and socio-demographic characteristics of the two study groups. Results A total of 926 mothers were beneficiaries of Janani Suraksha Yojana (JSY) program while 933 mothers were beneficiaries of augmented Arogya Laxmi Scheme (ALS). Mothers in ALS group (AOR 1.71; 95% CI 1.21-2.43) were at increased odds of having more than eight antenatal care (ANC) visits compared to the mothers availing JSY. Mothers in ALS group were at decreased odds of having complications like severe pain in the abdomen (AOR 0.43; 95% CI 0.22-0.86), swelling of legs or feet (AOR 0.59; 95% CI 0.44-0.80) compared to mothers in JSY group. Children of mothers in the ALS group had increased odds of receiving breastfeeding within 30 minutes of birth (AOR 1.46; 95% CI 1.13-1.88) compared to children of mothers in JSY group. Conclusions The newly launched augmented ALS led to the increased utilization of the government health facilities and improved the maternal and child health outcomes.